Characterization of the complete chloroplast genome of an important medicinal plant, Sinomenium acutum (Menispermaceae, Ranunculales). Issue 2 (2nd April 2020) - Hina, Faiza; Li, Junke; Chen, Chuan; Fu, Chengxin
Abstract: Sinomenium acutum is a woody vine of great virtue in traditional Chinese medicine and, nowadays, a potent anticancer drug against several types of cancers. In the present study, we have assembled and characterized the very first chloroplast (cp) genome sequence of S. acutum. The whole chloroplast genome is 162, 966 bp in length, containing a pair of inverted repeats (IR) of 25, 051 bp each, separated by one large single-copy region (LSC, 91, 627 bp) and a small single-copy region (SSC, 21, 237 bp). The cp genome encodes 132 unique genes that contain 85 protein-coding genes, 37 transfer RNA genes, and 8 ribosomal RNA genes. In our phylogeny of Ranunculales, Menispermum dauricum is sister to S. acutum .